Variability of flowering sex and its effect on agronomic trait expression in white guinea yam - Iseki, K.; Matsumoto, R.; Olaleye, O.; Shimizu, M.; Asfaw, A. (Frontiers Media, 2022)
White Guinea yam (Dioscorea rotundata) is mainly a dioecious tuberous crop that produces flowers of varying sex phenotypes. Agronomic traits in Guinea yam differ according to the sex phenotype, but the precise interaction between the traits and sex phenotype is not clearly understood. This might be due to the high heterozygosity of yam where cultivars with different flowering sex have different genetic backgrounds, which mask the sole effect of sex phenotype on the agronomic traits. This study used F1-derived clonal progenies from a bi-parental cross to minimize the impact of different genetic backgrounds among the plants with different sex phenotypes. The impact of plant sex on agronomic traits, specifically tuber yield, was evaluated through field trials conducted for four years. The results showed that only plants with a female genotype exhibited varying sex phenotypes even within the clones of same accession grown in the same experimental field. The significant effects of sex genotype and phenotype on agronomic traits were detected. Our results revealed that the flowering date was delayed in the plants with female genotypes compared to male genotypes, even when compared only among the plants with male phenotypes. The flowering date is the most important reason for the sexual differences in tuber yield. A high tuber yield was obtained when plants with the female phenotype flowered before tuber enlargement. This result can be attributed to the fact that the low flowering intensity in female plants increases the availability of carbon resources for leaf development. Female plants also showed a large negative effect of late flowering on tuber yield owing to resource competition between flowering and tuber enlargement. These findings demonstrate the feasibility of yield improvement by controlling the flowering time, with a higher effectiveness achieved in female than in male plants.